PERSEPSI BIAYA PENDIDIKAN, MOTIVASI TERHADAP PILIHAN KARIR PAJAK MELALUI MINAT MENGIKUTI BREVET PAJAK SEBAGAI INTERVENING - Puspita, Dyah Aruning; Setiawan, Januar Agung; Sugiono, Djoko (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2024)
The purpose of this research is to find out how much influence the cost of education has on social motivation and career motivation in taxation career choices through interest in participating in brevet as an intervening variable at STIE Malangkucecwara(ABM). Data source using primary data and sampling techniques using purposive sampling with the number of samples 105 respondents using SmartPLS 3.0. The results of the research on the variable costs of education, social motivation and career motivation have no effect on career choices in the field of taxation, while tax brevets can intervene social motivation and career motivation with career choices in the field of taxation